Impact of Academic Self-Efficacy on Entrepreneurial Intention of Faculty of Sport Sciences' Students: Bayburt University - Adatepe, Eda; Unlu, Yilmaz (Asian Journal of Education and Training, 2022)
This study aimed to determine the academic self-efficacy and entrepreneurial levels of the students studying in the faculties of sport sciences, to define the factors affecting these characteristics and to determine their impacts. In this study, the Entrepreneurial Scale for University Students and the Academic Self-Efficacy Scale were applied to 372 students studying at the faculty of. sport sciences. According to analysis results of the data obtained, it has been determined that the entrepreneurial levels of the students participating in the research are high. Entrepreneurial levels of male students are higher. than female students. Positive relationships were found with respect to the age variable in the dimensions of entrepreneurship and cognitive practices. BPT (Basic Proficiency Test) score has positive significant relations with entrepreneurship, cognitive practices and technical skills and CGPA has positive significant relations with academic self-efficacy scale sub-dimensions. As the work experience period of the students increased, the acquired level of entrepreneurship also increased. Moreover, as their academic self-efficacy increased, their entrepreneurial intentions also increased. The results obtained include empirical evidence that academic self-efficacy has a statistically significant. and positive impact on entrepreneurial intention. Therefore, higher education institutions should focus on improving the academic performance of students studying in undergraduate, associate and graduate education in order to increase their intention to create new job opportunities. Since this study only includes the opinions of the students of the faculty of sport sciences, it is recommended to expand the sample group and investigate the effect of different variables on entrepreneurial intention.